2012
DOI: 10.5251/abjna.2012.3.4.154.168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inter-specific interaction of nitrogen fertilizer and bean-maize cropping systems on quality of bean seed in Western Kenya

Abstract: Common bean (Phaseolus vulgaries) is an important crop in Kenya. Good quality seed availability for farmers is usually a major constraint. Bean seed quality is often affected by soil deficient nutrients and suboptimal intercropping systems practiced by farmers. Combined effects of N fertilizer at 0 kg N per ha, 50 kg N per ha and cropping systems comprising of four patterns namely Research, Farmers, Mbili mbili and pure bean stand practices were studied and evaluated in an intercrop involving beans and maize (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…These results are in line with the research conducted by Ożzütrk (2010), who found that TSW in winter rapeseed (Brassica napus L.) showed a steady increase when N rate increased from 0 to 150 kg ha −1 N, as well as consistent with studies in lentil (Lens culinaris Medik.) (Rahman et al 2013), common kidney bean (Phaseolus vulgaris L.) (Ogutu et al 2012), winter wheat (Triticum aestivum L.) (Mohammad and Ataei 2013), and mustard [Brassica juncea (L.) Czern.] (Mozaffari et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with the research conducted by Ożzütrk (2010), who found that TSW in winter rapeseed (Brassica napus L.) showed a steady increase when N rate increased from 0 to 150 kg ha −1 N, as well as consistent with studies in lentil (Lens culinaris Medik.) (Rahman et al 2013), common kidney bean (Phaseolus vulgaris L.) (Ogutu et al 2012), winter wheat (Triticum aestivum L.) (Mohammad and Ataei 2013), and mustard [Brassica juncea (L.) Czern.] (Mozaffari et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Relative to its effect on maize, fertiliser plus manure treatment did not influence bean yield in the maize-bean intercrops (Table 4), owing to intra-specific competition, where beans are generally outcompeted by maize. Notably, maize has higher competitive abilities for nutrients than beans under a bean-maize intercrop (Ogutu and Owuoche, 2012). As such, higher yields in pure stands could be attributed to a lack of competition for nutrients, water and other environmental resources.…”
Section: Discussionmentioning
confidence: 99%
“…Seed weight was taken after seeds had been threshed, winnowed and dried to moisture content of 14% as recommended by Ogutu et al (2012).…”
Section: Yield Datamentioning
confidence: 99%